GLOSSOPHOBIA IN ACADEMIC SPEAKING CONTEXTS: PERCEIVED COGNITIVE, EMOTIONAL, AND BEHAVIOURAL EFFECTS AMONG EFL PRE-SERVICE TEACHERS - Naurah, Faiza; Putra, M. Hadi Dwi; Tusya'Diah, Syakila; Irsyah, Lyra Vierdha; Mulia, Intan Tri; Jaya, Hariswan Putera (English Community Journal, 2026)
The college students frequently struggle with glossophobia, also known as public speaking anxiety, particularly those who are in charge of making academic presentations. This study explores the influence of glossophobia on fifth-semester students in the English Education Study Program at Sriwijaya University. A 12-item Likert scale questionnaire evaluating four dimensions, physical symptoms, perceived cognitive and emotional effects, perceived performance effects, and behavioural responses that was used to gather data from 50 students using a quantitative approach. According to the findings, students' anxiety levels ranged from moderate to severe, with cognitive and emotional discomfort showing the most effects. Anxiety nevertheless affected presentation delivery, clarity, and fluency even if the effect on performance was only minor. These findings suggest that glossophobia significantly is perceived to influence students’ perceived academic performance and underscore the need for supportive pedagogical strategies to reduce anxiety and enhance students’ confidence in public speaking.